Rancang Bangun Sistem Informasi Pengendalian Piutang Usaha pada CV. Hasil Sukses - Ananda, Aldy Hafil; Soebijono, Tony; Oktaviani, Oktaviani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV. Hasil Sukses exist as seeing the many end users are start to switch from using of conventional wooden roof to galvalum lightweight and anti-termite, so it can last for decades and does not require regular maintenance like wood. CV. Hasil Sukses engaged in procurement galvalum APLUS brand. CV. Hasil Sukses’ galvalum brought directly from the factory. The scope of the company is taken as a supplier for the agency, shop building, and applicators (installer galvalum).Problems on the CV. Hasil Sukses today is accounts receivable that can not be controlled, because the recording of transactions are still using manual processes and are recorded using note board so could not archived properly. Manual recording of transactions and accounts receivable system and filing a memorandum that is not good cause problems in terms of billing. Billing Division at companies often spend time billing to consumers resulting company would have to pay in advance with the manufacturer for CV. Hasil Sukses themselves also do a credit for making the goods.The trial results and internal evaluation showed that the resulting information system capable of helping finance the CV. Hasil Sukses to collect on time. So that companies no longer need to pay in advance with the manufacturer.